Synthesis of Medium Entropy Coatings and Study of the Influence of Bias Voltage and Nitrogen Flow on Their Microstructural and Tribological Properties (2024)
TiTaZrNb medium entropy coatings and their nitride forms (TiTaZrNb)Nx were synthesized by direct current magnetron sputtering. The study evaluated the bias voltage affects microstructure, chemical and phase composition of the metallic coatings. Also, the effect of nitrogen flow on the microstructural and tribological properties of the corresponding nitrides was studied. A change in the crystalline structure from BCC for TiTaZrNb coatings to FCC for (TiTaZrNb)Nx was observed. It was associated with the incor- poration of nitrogen into the matrix and the consequent formation of a solid solution of (TiTaZrNb)Nx. An increase in the hardness and residual stresses of the metallic coating was observed with increasing bias voltage to 2 130 V and of the nitride coating with increasing nitrogen flow to 12 sccm, reaching hardness values of 12.8 GPa and 25 GPa, respectively. A slight reduction in the hardness of the deposited nitride coating was observed at the higher nitrogen flow of 15 sccm, probably due to the formation of the TiN and ZrN phases. The higher hardness and lower wear rate of the (TiTaZrNb)Nx nitride coatings compared to the uncoated M2 steel samples demonstrate the protective effect against wear of these coatings.